Effet de l’hypovitaminose D sur l’hyperparathyroïdie secondaire chez les patients hémodialysés dans la localité de Mostaganem. - Kerdagh, Amina (My University, 2021)
Historically, many scientific studies have converged on the same result; it’s that vitamin D is the main steroid hormone from which its presence is essential for the regulation of many metabolisms. Currently, various recent research has revealed that the action of prohormone D, exceeds the prevention of rickets and osteomalacia. Secondary hyperparathyroidism to vitamin D deficiency is very common in hemodialysis. The purpose of this study is to assess hypovitaminosis D and hypersecretion of parathormone of the parathyroid gland during chronic end-stage renal failure from clinical data and assays of 25-OH D, parathormone, renal balance and phosphocalcic parameters. In 22 hemodialysis patients aged 31 to 61 years. In our study hypovitaminosis D was observed in (81.81%) hemodialysis patients with secondary hyperparathyroidism. Our results show over all the absence of a disturbed phosphocalcic balance due to calcium supplementation for the calcium balance, and it’s also due to the right consuming of the treatments and of course following a certain diet for phosphatic balance. Finally, the study showed that, compared to the thresholds admitted in dialysis, (4.45%) hemodialysis was in the recommended target.
Keywords: Hypovitaminosis D-Secondary Hyperparathyroidism-PTH-Calcemia, Phosphoraemia-Hemodialysis.